Deconstructing Rape by Fraud - McJunkin, Ben A. (Columbia Journal of Gender and Law, 2014)
In this Article, I critically examine the role of normative masculinity in determining the shape and scope of the criminal law doctrine of rape by fraud, which purports to criminalize sexual intercourse procured through certain material deceptions. In application, the rape by fraud doctrine is exceedingly narrow—deceptively induced sexual intercourse is rarely criminalized as rape, despite deception’s profound impact on the voluntariness of sexual consent. As the Article explains, the rape by fraud doctrine is thus in tension with the prevailing view that rape law principally protects a thick norm of individual sexual autonomy. Despite this tension, the narrowness of the rape by fraud doctrine is frequently defended, often by those who are most committed to individual autonomy elsewhere in rape law. Through an analysis of court decisions and academic commentary, I demonstrate that those defenses largely rest on appeals to a romanticized ideal of the practice of seduction. I illuminate the link between seduction and a prevailing ideology of normative masculinity that allocates social status for men on the basis of demonstrations of sexual conquest. That ideology perpetuates narratives in which women, through their capacity to grant or withhold consent, hold power over men when pursued as objects for sex. Indeed, within this account, the transgression of women’s power is what makes sexual conquest worthy of masculine status. Deceptions used to procure sex are criminalized only in exceptional cases where the narratives of interpersonal power break down. Thus, the rape by fraud doctrine can be seen as codifying existing limits on masculine status transfer. Ultimately, I argue that understanding the rape by fraud doctrine in terms of normative masculinity exposes an important continuity between contemporary rape law and rape law historically, in which rape was a crime against men’s property interest in women.